2011
DOI: 10.5771/0935-9915-2011-2-132
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Work Ability and Work Motivation of Lower-educated Older Workers: Directions for Work Redesign

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…In general, the study results show that older employees gave the highest rankings to social characteristics, then motivational characteristics, and then contextual characteristics. Therefore, the findings expand knowledge of these work characteristics and support the relevance of social work characteristics [58] in relation to suitable work design for older workers.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In general, the study results show that older employees gave the highest rankings to social characteristics, then motivational characteristics, and then contextual characteristics. Therefore, the findings expand knowledge of these work characteristics and support the relevance of social work characteristics [58] in relation to suitable work design for older workers.…”
Section: Discussionsupporting
confidence: 64%
“…Both social characteristics are also quoted frequently by the participants. Improving social support for older workers shows desirable effects on work ability and work motivation [58].…”
Section: Discussionmentioning
confidence: 99%
“…One is associated with the question of how to retain the working commitment of older workers, who are often prematurely lost to the workforce, raising the costs to society of their retirement and contributing to social isolation and health deterioration. An interesting study on this question has been conducted by Sanders et al (2011), using longitudinal data from the Netherlands Working Conditions Study. They examine the work ability and motivation of less educated workers over 45 years of age, using an augmented version of Hackman and Oldham's (1980) job characteristics model.…”
Section: Where Is the Management Discipline Of Hrm Taking Us?mentioning
confidence: 99%
“…Many working conditions can change due to a voluntary employer change, which may have a direct impact on work ability-and of course job satisfaction-such as leadership quality, work-privacy conflict, travel time to work, colleagues, work tasks, influence at work, working environment and work equipment (Grund 2009;Carless and Arnup 2011;Garthe and Hasselhorn 2020). Several studies confirmed the relationship between physical and psychological working conditions and work ability (Alavinia 2008;van den Berg et al 2008;Sanders et al 2011;Attarchi et al 2014;Weale et al 2019). It can also be assumed that only those employees change, who expect an improvement, which implies that changers to some degree may constitute a selective group.…”
Section: The Honeymoon-hangover Effect For Work Abilitymentioning
confidence: 98%